Model EIA terintegrasi untuk penilaian dampak lingkungan PLTS Rooftop perumahan di Kota Medan - Ronald Naibaho; Andi S. Nasution; Parlindungan Pasaribu (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2026)
This research aims to develop an environmental impact assessment model for rooftop solar power plants (PLTS rooftop) in residential areas of Medan City, using a structured and contextual Environmental Impact Assessment (EIA) approach. The model is designed to integrate biophysical, socio-environmental, and technical-safety aspects, making it a practical evaluation tool for local stakeholders. The research method used is descriptive-quantitative with three main stages: identification of impact aspects and indicators, development of a scoring and weighting matrix based on expert judgment, and application of the model to 30 simulated houses with the potential to install rooftop PLTS. Each housing unit was assessed based on the formulated indicators, then the total impact value was calculated and classified into low, medium, and high categories. The novelty of the research lies in the development of an EIA model specifically for residential-scale rooftop PLTS in Medan City, incorporating indicators such as roof temperature, water runoff, glare, building structure, social acceptance, inter-neighbor conflict, and the risks of cables, fire, and panel waste within a single integrated assessment framework. The research results show that the biophysical aspect has the highest average score (3.17), followed by the technical-safety aspect (2.95) and the socio-environmental aspect (2.77), with an average total value of 2.96 and the majority of houses falling into the medium impact category. These findings indicate that rooftop PLTS is relatively feasible for implementation in Medan's residential areas, provided there is adequate technical mitigation and social aspect management, and confirm that the developed EIA model is effective as an environmental impact assessment instrument at the micro-settlement level.